Faktor Non-Yuridis Dalam Pembentukan Peraturan Daerah Kota Surabaya - Nany Suryawati; Victor Imanuel W Nalle (Jurnal Paradigma Hukum Pembangunan, 2016)
The legislation process is not only influenced by the juridical factor. Non-juridical factors also influence the legislative process. Even non-juridical factors influence sometimes is greater than juridical factors. Whereas any legislation must meet the criteria of good legislation based on legisprudence theory. The quality of legislation in DPRD Kota Surabayais also influenced by other factors beyond the text of the legislation. Therefore, it is the legislative process in DPRD Kota Surabaya interesting to analyze because of course non-juridical factors remain influential in the legislative process. These factors, however, can be accommodated in such a way to suit the demands of judicial aspect. The analysis in this study isconducted by a socio- legal approach. Based on the research by socio-legal approach, the legislation process in DPRD Kota Surabaya (2009-2014) is influenced by non-juridical factors. Non-juridical factors are influenced by the interests of the struggle for influence in the community base. On the side of the legislator, there is an interest to build a base of constituents on an on going basis. On the executive side, there is the need to build a public trust in the government. The interests of each other in the dynamics of the discussion of draft legislations relating to the budget.